Human Resource Practices As Determinants Of Employee Turnover: An Empirical Investigation - Bawa, Muhammad Aminu; Muhammad Jantan, Muhammad Jantan (Asian Academy of Management (AAM), 2005)
The volume of literature on the causes of employee turnover continues to grow. In spite of this, attempts to distinguish between the causes of voluntary and involuntary turnover in organizations, though recognized for quite some time, receive little attention from researchers. The two phenomena seem to be influenced by a different set of factors. There are clear-cut theoretical and empirical reasons for this assertion. The objective of this paper is to investigate the relationship between human resource (HR) practices and employee turnover in Malaysia where companies are generally experiencing labour shortage and labour turnover. Using data collected from a census of managers, the study utilized Analysis of Variance (ANOVA) and simple regression and tested hypotheses developed to investigate the relationship between HR practices and employee voluntary and involuntary turnover. The results show that (1) staffing process and employee monitoring were effective in reducing involuntary turnover, and (2) none of the HR practices were effective in reducing voluntary turnover. In other words, workers continue to leave or quit irrespective of the type of HR practices implemented. The paper concludes that economic factors such as availability of alternative jobs are most likely relevant in explaining the turnover process. Based on these findings, various strategies were suggested which have wider managerial and policy implications for the management of turnover in similar settings.